(untitled) (World Bulletin of Public Health, 2022)
People of all ages all over the world are experiencing a serious health crisis brought on by COVID-19. Initial reports suggested the illness was localised to the lungs. Some new research, however, has defined the effects of COV-19 on male and female reproductive systems. . In Further, COVID-19 mediator effects, such as renin-angiotensin system disruption, oxidative stress, and inflammation, Influences of cytokine storm, fever, and psychological stress on reproductive physiology have also been explored , COVID-19 increased body temperature, oxidative stress, and cytokine storm that are all mediated by in-patient gametogenesis, steroidogenesis, and menstrual cycles. Last but not least, being shut away from other people, Stress and dissatisfaction brought on by uncertainty about one’s employment have been shown to elevate glucocorticoid-mediated poor quality sperm in males and an increased chance of miscarriage in females. This explains why the impact Evidence of the effect of COVID-19 on fertility and reproductive health is strong. method a cross-sectional survey was administered to Iraqi women who are either making plans for or are presently undergoing treatment for infertility. In the middle of July of 2020, a digital survey questionnaire was sent over a range of social media platforms, including websites dedicated to women’s health and fertility in Iraq Results.Participant demographic and reproductive characteristics are given . CONCLUSION Despite the fact that this review’s findings reveal substantial changes in menstruation, recovery of normal ovarian reserve and hormone levels; transient, mild alteration. When it comes to having children, The greatest effect of covid.19 infection was a decrease in both the quantity and quality of birds. and embryos